First and Second Reports Expenditure Reforms Commission - Planning Commission (Planning Commission, 2000)
The background leading to the establishment of this Commission and also the Terms of Reference are set out in this Resolution, a copy of which is at Annexe-I. The Commission is to give its final report within a period of one year. The Resolution also provides for the Commission to forward its recommendations to the Government on a quarterly basis.
Government of India Ministry of Finance
Government of India Ministry of Finance